Current status of presurgical infant orthopaedic treatment for cleft lip and palate patients: A critical review - P. Priyanka Niranjane; R. H. Kamble; S. Pallavi Diagavane; S. Sunita Shrivastav; Puneet Batra; S. D. Vasudevan; Pushkar Patil (Indian Journal of Plastic Surgery)
Rehabilitation of cleft lip and palate (CLP) patients is a challenge for all the concerned members of the cleft team, and various treatment modalities have been attempted to obtain aesthetic results. Presurgical infant orthopaedics (PSIO) was introduced to reshape alveolar and nasal segments prior to surgical repair of cleft lip. However, literature reports lot of controversy regarding the use of PSIO in patients with CLP. Evaluation of long-term results of PSIO can provide scientific evidence on the efficacy and usefulness of PSIO in CLP patients. The aim was to assess the scientific evidence on the efficiency of PSIO appliances in patients with CLP and to critically analyse the current status of PSIO. A PubMed search was performed using the terms PSIO, presurgical nasoalveolar moulding and its long-term results and related articles were selected for the review. The documented studies report no beneficial effect of PSIO on maxillary arch dimensions, facial aesthetics and in the subsequent development of dentition and occlusion in CLP patients. Nasal moulding seems to be more beneficial and effective in unilateral cleft lip and palate patients with better long-term results.